2015
DOI: 10.1111/jcmm.12720
|View full text |Cite
|
Sign up to set email alerts
|

CYP1A1 rs1048943 and rs4646903 polymorphisms associated with laryngeal cancer susceptibility among Asian populations: a meta‐analysis

Abstract: Many studies have investigated the association between CYP1A1 rs1048943 and rs4646903 polymorphisms and laryngeal cancer risk, but their results have been inconsistent. The PubMed and CNKI were searched for case–control studies published up to 01 July 2015. Data were extracted and pooled odds ratios (OR) with 95% confidence intervals (CI) were calculated. In this meta‐analysis, we assessed 10 published studies involving comprising 748 laryngeal cancer cases and 1558 controls of the association between CYP1A1 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 25 publications
1
10
0
4
Order By: Relevance
“…Meta‐analyses evaluating the effect of CYP19A1 *19C>T , CYP1A1 Ile462Val , CYP1B1 Leu432Val and COMT Val158Met did, in line with our study, not find any significant associations with breast cancer risk. For CYP19A1 *19C>T and COMT Val158Met, no associations were found overall or when stratifying by ethnicity .…”
Section: Discussionsupporting
confidence: 89%
“…Meta‐analyses evaluating the effect of CYP19A1 *19C>T , CYP1A1 Ile462Val , CYP1B1 Leu432Val and COMT Val158Met did, in line with our study, not find any significant associations with breast cancer risk. For CYP19A1 *19C>T and COMT Val158Met, no associations were found overall or when stratifying by ethnicity .…”
Section: Discussionsupporting
confidence: 89%
“…In addition, Lourenço et al studied 142 patients with head and neck squamous cell carcinoma and 142 control subjects and found that CYP1A1, GSTM1 and GSTT1 were closely related to head and neck cancer especially in patients with a severe smoking level 15 . A meta-analysis in 2016 found that carriers of the G allele for CYP1A1 rs1048943 and rs4646903 had a significantly increased risk of laryngeal cancer in Asian populations; 10 trials were included in the study, involving 748 patients with laryngeal cancer and 1558 control subjects 16 . These results are consistent with the present finding suggesting that allele G carriers at rs1048943 have an increased risk of laryngeal carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…xenobióticos (Ingelman-Sundbarg, 2004;Nebert e Dalton, 2006 (Tanimotoa et al 1999;Sato et al, 2000;Ho et al, 2007;Singh et al, 2014;Yu et al, 2014;Zeng et al, 2016). Porém tais associações são controversas em alguns estudos.…”
Section: Genes Envolvidos Na Metabolização Do Tabacounclassified
“…A variante CYP1A1*2C (rs1048943), que corresponde à troca da base A pela G, com alteração do aminoácido isoleucina para valina (Colombo e Rahal, 2009;Yousef et al, 2012), produz também uma enzima de atividade aumentada, que tem sido associada ao aumento do risco de desenvolvimento de neoplasias da cavidade oral e da laringe em populações Asiáticas (Sato et al, 2000;Zeng et al, 2016).…”
Section: Genes Envolvidos Na Metabolização Do Tabacounclassified
See 1 more Smart Citation